The elusive Ethiopian "middle class": constructed from outside, inexistent from inside? - (:unkn) unknown (My University, 2013)
Panel Middle classes in Africa: the making of social category and its social meaning and uses mod. Dominique Darbon, Dieter Neubert (Université de Bayreuth) et Comi Toulabor http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2013
Keywords: African Research